ASURANSI DALAM PERSPEKTIF ISLAM - Risna Wati (Muadalah : Jurnal Hukum, 2023)
In life no one can predict what will happen in the future perfectly, even by using various analytical tools. Risks in the future may occur to a person's life, for example, death, illness or the risk of being fired from his job. In the business world, risks that can be faced can be in the form of risk of loss due to fire, damage or loss or other risks. Every risk that will be faced must be handled so as not to cause even greater losses. To overcome unwanted risks in the future, it is necessary to have a company that is willing to bear the risk, such as an insurance company. As we know, insurance is a mutual agreement between members of the community to guarantee and guarantee each other by raising money and creating a joint financial savings fund that is used as a relief fund for someone who is overwritten by difficulties. This is done as an effort to deal with events that might happen to someone and lead to losses. Apart from that , the community is insured and the large number of Muslims involved in it , makes this problem urgent to know its position from an Islamic perspective . However, because this insurance issue is not explicitly explained in the text, the problem is seen as ijtihadi. Departing from these problems , the study of insurance in Islamic perspective is very interesting . In addition to seeing the pros and cons as well as the " middle way " to these problems . And also see how the development of insurance in Indonesia whether insurance is permissible under Islamic law